(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Katishula (Low back pain) is enumerated under Vatajananatmajavikara. References on Katishula are found scattered in Samhitas. To arrive at specific diagnosis of a disease, manifestation of specific symptoms are very essential. But when such symptoms are not completely manifested or the symptoms appear in the feeble strength or do not appear at all, method of trial and error intervention becomes helpful to arrive at correct diagnosis. This is achieved through Upashaya, that which gives Sukhanubandha. Hence present study was planned and undertaken to explore the role of Shunthi churna udvartana as Upashaya of Katishula against Gunas of Vata. Vata is attributed with Gunas like Ruksha, Laghu, Sheetha, Khara, Sukshma and Chala. Shunthi churna possesses Ushnaguna and is ascribed with Shoolaprashamana property. In the present study 30 patients of Katishula underwent intervention with Shunthi churna udvartana in Katipradesha twice daily in empty stomach, in the morning and evening for 3 days and were observed for relief in Katishula after the intervention. Significant relief in Katishula (Pain in Kati pradesha) was noted. On subjecting the result to Statistical analysis, mean score obtained in 30 patients before intervention with Shunthi churna udvartana was 7.26, which reduced to 2.96 after intervention. The mean difference is 4.3. Further on application of paired student t test p-value was <0.001, which is statistically highly significant. Hence it is evident that Shunthi churna udvartana has a definite role in relieving Katishula, specifically pain by its Ushnaguna and Shula prashamana property against Sheethaguna of Vata causing Katishula.